Value-based medicine and precision medicine in anaesthesia - Md Ralib, Azrina; Shariffuddin, Ina Ismiarti (Kugler Publications, 2022)
Evidence-based medicine has become the part and parcel of the practice of medicine nowadays. It integrates patient preference with evidence and clinicians’ experience, leading to the improvement in the length of life.1 However, concern arises that it does not consider quality of life; hence, the concept of value-based medicine has become increasingly popular. Value-based medicine incorporates patient-perceived values that emphasise quality of life. In addition, it also considers the cost of intervention, the goals of which is to improve the quality of health care and efficient use of resources. The concept was first introduced by Brown et al., who defined it as “the practice of medicine incorporating the highest level of evidence-based data with the patient-perceived value conferred by health care interventions for the resources expended.”